Background and language of the Narum community in Marudi, Sarawak - Sa’adiah Ma’alip,; Syaidul Azam Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Narum community is located in Marudi, Sarawak and belongs to a minority language community that is heading towards language extinction. In terms of language cognate, there are similarities between the language of the Narum community and the Kenyah community. However, the number of speakers of this language is declining and the number who can master the Narum language well, especially the younger generation is very limited. This puts the language of this minority community in a threatened position. This is a preliminary study aimed to introduce this language community. Data collection was gathered to document the linguistic and cultural situation practised in this language community. In this study, qualitative methods were applied. The data was collected by interviews to obtain data directly from this language community. The findings of this study describe the linguistic and cultural situation of the Narum language community. The attitude of the native speakers who do not pay much attention to their heritage has become one of the causes of the language of this community is increasingly threatened, in fact, this community is also increasingly unknown for their existence. In addition, intermarriage also contributes to the loss of the language of the Narum community and will also destroy the identity of this community. Indeed, it would be a huge loss if this minority community became extinct. Therefore, immediate action needs to be taken to save and preserve it. It not only needs to be immediately recorded and documented, but more importantly, these language communities need to use and know their history and language actively in order to preserve and revitalize their language and cultural heritage for future generations.